Mobile RNAs as systemic signaling beyond boundaries for plant stress resistance - Lin, Shujin; Li, Haining; Bai, Shiyan; Han, Xiao (Frontiers in Plant Science, 2026)
Plant mobile RNAs—including small RNAs (miRNAs, siRNAs), mRNAs, lncRNAs, and tRNA fragments—function as systemic signaling molecules that traverse cellular, tissue, and species boundaries to coordinate plant adaptation to environmental stresses. Here, we summarize the critical roles of mobile RNAs in mediating systemic adaptation to abiotic challenges and biotic interactions. Crucially, we highlight the diverse transport mechanisms enabling their movement and discuss the emerging functional versatility of mobile RNAs, which extends beyond transcriptional regulation to encompass epigenetic modifications, resource allocation, and cross-species communication. These fundamental insights are driving transformative applications: Mobile RNAs provide the foundation for developing systemic RNAi-based biopesticides and are being integrated with CRISPR-Cas technologies to overcome delivery barriers and enable heritable, transgene-free genome editing in crops. Understanding and harnessing mobile RNA networks offers unprecedented potential for engineering resilient crops and implementing precise, sustainable crop protection strategies to address global food security challenges.